Biaxial Elongation Behavior in Partially Molted State of Two-Layer Sheets Containing Postconsumer Material - Wittmann, Lisa-Maria; Kaschta, Joachim; Drummer, Dietmar (Polymers, 2022)
Due to the lack of raw material and forced by political demand, an increasing percentage of postconsumer materials (PCR) shall be used in all processing methods in polymer technology. Thermoforming, as one of the oldest polymer-processing methods, has special requirements regarding the melt stability at high temperatures. Low melt stability affects the thermoforming in a negative manner, as the low stiffness leads the sheet to sag during the heating phase. In this study, two-layer sheets are used in order to improve melt stability of PCR material. The focus is placed on the influence of rheological properties on the biaxial stretching behavior of mono- and two-layer sheets in partially molted state. In order to create a stabilizing layer, two different thermoformable virgin materials with a melt flow rate (MFR) of 3 g/10 min and 6 g/10 min were chosen. The second layer consists of instable PCR materials with a MFR of 16 g/10min and 50 g/10 min. Rheological investigations, molecular characterization and biaxia tretching tests are used to show the benefit of two-layer sheets for processing PCR material under elongational stress. The results show that the use of two-layer sheets can improve the biaxial stretching properties, so that two-layer sheets can offer a significant potential in the processing of PCR materials in thermoforming.<br

Elongation behaviour of filled semi-crystalline polymers in thermoforming - Wittmann, Lisa-Maria; Kurth, Katharina; Drummer, Dietmar (Advances in Materials and Processing Technologies, 2020)
Thermoforming, besides injection moulding and extrusion, belongs to the most important processes of polymer processing. Thin sheets are formed to parts in a so-called stretch-forming process. The properties of the finally formed parts depend on the sheet properties. Amorphous polymers such as polystyrene and polymethylmethacrylate are examples for most popular polymers used in thermoforming because of their wide temperature ranges suitable for processing with thermoforming. Crystalline polymers or reinforced amorphous polymers have a smaller forming window compared to these amorphous polymers but offer several other advantages. For the processing of most crystalline polymers, modifications of the thermoforming process as well as the materials themselves are necessary. This study analyses the influence of fillers on the elongation behaviour of polyeythlene. Furthermore, the interaction between fillers and cross-linking is investigated in thermoforming experiments as well as microscopical analysis. The general aim is to expand the process related knowledge on material behaviour to qualify more semi-crystalline materials for processing in technical thermoforming applications. In this study, the enormous benefit of radiation crosslinking on the elongation behaviour during thermoforming of filled systems could be presented. Subsequent crosslinking of the filled systems enable the thermoforming of filled films, which could not be processed without irradiation.
CRIS-Team Scopus Importer:2023-03-29
Keywords: cross-linking; fillers; glass spheres; semi-crystalline polymers; Thermoforming

Hochgefüllte Kunststoffe: Neue Potenziale durch den Einsatz von Füllstoffen zur gezielten Eigenschaftsmodifikation - Drummer, Dietmar; Grützmacher, Constanze; Kleffel, Tobias; Lanzl, Lydia; Rösel, Uta; Roth, Benedikt; Schneider, Kevin; Tomiak, Florian; Wittmann, Lisa-Maria (Jahresmagazin Ingenieurwissenschaften, 2021)
Die Anforderungen an Kunststoffbauteile erfordern meist den Einsatz von Füll- und Verstärkungsstoffen sowie Additiven zur gezielten Modifikation des Eigenschaftsprofils. In diesem Beitrag werden aktuelle Forschungsschwerpunkte des Lehrstuhls für Kunststofftechnik (LKT) in der Verbesserung von mechanischen Eigenschaften und dem gezielten Einstellen von flammschützenden, elektrischen, dielektrischen und magnetischen Eigenschaften zur Bauteilfunktionalisierung vorgestell
Keywords: Gefüllte Systeme in der AF; Flammschutz durch synergistische Wirkstoff-Kombinationen; Mehrschichtfolienextrusion; Thermoformen; Bipolarplatte; dreidimensionale Schaumstoffbauteile im Hochfrequenzschweißverfahren; Duroplastbasierte Kunststoffgebundene Dauermagnete

Influence of an Increased Fiber Filler Content on the Elongational Behaviour of Filled Films in the Thermoforming Process - Wittmann, Lisa-Maria; Wolf, Michael; Drummer, Dietmar (American Journal of Mechanical and Materials Engineering, 2019)

Influence of radiation-crosslinking on the elongation behaviour of glass-fibre-filled sheets in the thermoforming process - Wittmann, Lisa-Maria; Wolf, Michael; Kurth, Katharina; Drummer, Dietmar (Journal of Polymer Engineering, 2019)

Influence of Stitching Parameters on the Joint Strength of Welded-Stitched Composites - Wittmann, Lisa-Maria; Kleffel, Tobias; Mattner, Tobias; Drummer, Dietmar (International Polymer Processing, 2018)

Investigating the Integration of Nonwoven Carbon Fibers for Mechanical Enhancement in Compression Molded Fiber-Reinforced Polymer Bipolar Plates - Frank, Rainer; Wittmann, Lisa-Maria; Kleffel, Tobias; Roth, Benedikt; Graichen, Knut; Drummer, Dietmar (Polymers, 2023)
The demand for polymer composite solutions in bipolar plates for polymer electrolyte membrane fuel cells (PEMFCs) has risen due to advantages over metal plates such as longer lifetime, weight reduction, corrosion resistance, flexible manufacturing, freedom of design, and cost-effectiveness. The challenge with polymer composites is achieving both sufficient electrical conductivity and mechanical stability with high filler content. A carbon fiber fleece as reinforcement in a graphite-filled polypropylene (PP) matrix was investigated for use as bipolar plate material with increased mechanical and sufficient conductive properties. Plates with a thickness of 1 mm containing four layers of fleece impregnated in the PP-graphite compound were produced in a compression molding process. Particle and fiber interactions were investigated via microscopy. The plates were characterized with respect to the electrical conductivity and mechanical stability. High electric conductivity was reached for fiber-reinforced and plain PP-graphite compound plates, with increased filler content leading to a higher conductivity. The contact resistance remained largely unaffected by surface etching as no polymeric skin layer formed during compression molding. Fiber-reinforced plates exhibit twice the tensile strength, a significantly higher tensile modulus, and an increased elongation at break, compared to PP filled only with graphite.
CRIS-Team Scopus Importer:2023-10-20
Keywords: bipolar plate; carbon fleece; compression molding; fiber reinforcement; fuel cell

Mechanical properties of thermoformed multilayer parts containing non thermoformable materials - Wittmann, Lisa-Maria; Drummer, Dietmar (Journal of Plastic Film & Sheeting, 2022)
Different viscous materials were chosen to simulate the behavior of degraded materials in the thermoforming process and to demonstrate the potential of using multilayer sheets for thermoforming non thermoformable materials without losing final part performance. The mechanical properties of thermoformed multilayer sheets with 3, 22, and 50 melt flow index (MFI) polypropylenes (PP) were investigated. Therefore, a thermoformable material (MFI-3) and difficult/non thermoformable (MFI-22 and MFI-50) material was combined in the bilayer sheet. The extruded bilayer sheets had equal layer thicknesses (A/B 50%/50%) and unequal layer thicknesses (A/B 70%/30%), whereby B is always the material difficult to thermoform. As the non thermoformable material can lead to inhomogenity in the wall thickness and therefore can cause different part performance, the investigation focused on how the non thermoformable material influenced the mechanical performance of the final part. This labortory scale thermoformability investigation of the extruded PP sheets with different viscosities showed that the low viscous layer position has only a marginal influence on the general mechanical properties of the thermoformed parts. The mechanical properties can be predicted more precisely by the mechanical properties of the thermoformable material used than by the rule of mixtures. Whereas the Young’s modulus and yield stress change only negligibly, the elongation at break after thermoforming significantly increases with the stable component.<br
Keywords: Thermoformability; multilayer sheets; mechanical properties; wall thickness; less viscous materials

Multilayer sheets for thermoforming non thermoformable polymers - Wittmann, Lisa-Maria; Drummer, Dietmar (Journal of Plastic Film & Sheeting, 2021)
Multilayer sheets were used for thermoforming non thermoformable polymers in order to face the challenge of semi-crystalline polymers like low melt-stiffness. Mono- and 2-layer sheets consisting of different polypropylene (PP) homopolymers were extruded on a twin screw extruder. The PP viscosity as was measured by melt flow rate (MFR) 3 g/10 min., 12 g/10 min., 22 g/10 min. and 50 g/10 min. The layer ratio was varied between the equal layer ratio (A50/B50) of the individual layers and the low (A30/B70) or high viscosity ratio (A70/B30). The extrusion results show that for extreme viscosity differences (MFR3 and MFR50), the critical layer ratios known from the literature are only valid to a limited extent. The critical viscosity ratio < 4, which is known from the literature, is much lower here and should be less than 3. The investigation of thermoformability on laboratory scale of the extruded PP sheets with different viscosities showed that the low viscous layer position has only a marginal influence on the general thermoformability. Thermoforming of materials that are not thermoformable, with a storage modulus of less than 10³ Pa and a ratio between storage and loss modulus (tan δ) greater than 1, becomes possible using a multilayer sheet independant of the layer ratio. If the layer with higher viscosity acts as a stabilizing layer, thermoforming is possible.
CRIS-Team Scopus Importer:2021-08-13
Keywords: multilayer; strain developement; Thermoformability; viscosity; wall thickness

Radiation Crosslinking of Films - New Applications in the Thermoforming of Filled Materials - Wittmann, Lisa-Maria; Fischer, Dirk; Drummer, Dietmar (Kunststoffe International, 2019)

Strahlenvernetzung von Folien - Neue Anwendungen bei der Verarbeitung gefüllter Materialien im Thermoformprozess - Wittmann, Lisa-Maria; Fischer, Dirk; Drummer, Dietmar (Kunststoffe, 2019)

Two Layer Sheets for Processing Post-Consumer Materials - Wittmann, Lisa-Maria; Drummer, Dietmar (Polymers, 2022)
An increasing percentage of post-consumer materials (PCR) is becoming more and more important in all processing methods in polymer technology, also due to the lack of raw materials and political demands. Very special requirements are placed on material properties such as viscosities in extrusion. Low viscosities and the presence of particles affect extrusion in a negative manner. In this study, the use of multilayer sheets is determined to both ensure extrudability and contribute to a significant improvement in surface qualities. The focus is placed on the influence of viscosity and particles on mono- und multilayer sheet quality. Therefore, two different virgin materials with a melt flow rate (MFR) of 3 g/10 min and 6 g/10 min and two different PCR materials with a MFR of 16 g/10 min and 50 g/10 min are processed both in monolayers and in two layer sheets. Rheological investigations, optical analysis, and film thickness distributions are used to show the relationship between matrix viscosity and particles. The results show that the use of multilayer extrusion can improve both extrudability and sheet quality, so that multilayer sheets can offer a significant potential in the processing of PCR materials.
CRIS-Team WoS Importer:2022-05-06